Empirical Analysis of Ethical Principles Applied to Different AI Uses Cases. - López Rivero, Alfonso José; Beato, M. Encarnación; Muñoz Martínez, César; Cortiñas Vázquez, Pedro Gonzalo (International Journal of Interactive Multimedia and Artificial Intelligence, 2022)
In this paper, we present an empirical study on the perception of the ethical challenges of artificial intelligence groups in the classification made by the European Union (EU). The study seeks to identify the ethical principles that cause the greatest concern among the population, analyzing these characteristics among different actors. The main study analyses the difference between Information and Communications Technology (ICT) professionals and the rest of the population. Along with this study, we conducted a gender study; in addition, we studied differences between university students, classified as future professionals who can work in Artificial Intelligence, and other university students. We believe that this work is a starting point for an informed debate in the scientific community and industry on the ethical implications of artificial intelligence based on the classification of ethical principles made by the EU, which can be extrapolated to any analysis carried out on the use of data to apply them in algorithms based on Artificial Intelligence.